Identifying factors influencing emerging innovations in hospital discharge decision making in response to system stress: a qualitative study - Allison M. Gustavson; Matthew J. Miller; Natassia Boening; Emily M. Hudson; Jennifer P. Wisdom; Robert E. Burke; Hildi J. Hagedorn (BMC, 2024)
Abstract Background The purpose of this qualitative study was to identify emergent rehabilitation innovations and clinician perceptions influencing their implementation and outcomes related to hospital discharge decision-making during the Coronavirus 2019 pandemic. Methods Rehabilitation clinicians were recruited from the Veterans Affairs Health Care System and participated in individual semi-structured interviews guided by the integrated Promoting Action on Research Implementation in Health Services (i-PARIHS) framework. Data were analyzed using a rapid qualitative, deductive team-based approach informed by directed content analysis. Results Twenty-three rehabilitation clinicians representing physical (N = 11) and occupational therapy (N = 12) participated in the study. Three primary themes were generated: (1) Innovation: emerging innovations in discharge processes included perceived increases in team collaboration, shifts in caseload prioritization, and alternative options for post-acute care. (2) Recipients: innovations emerged as approaches to communicating discharge recommendations changed (in-person to virtual) and strong patient/family preferences to discharge to the home challenged collaborative goal setting; and (3) Context: the ability of rehabilitation clinicians to innovate and the form of innovations were influenced by the broader hospital system, interdisciplinary team dynamics, and policy fluctuations. Innovations described by participants included (1) use of technological modalities for interdisciplinary collaboration, (2) expansion of telehealth modalities to deliver care in the home, (3) changes in acute care case prioritization, and (4) alternative options for discharge directly to home. Conclusions Our findings reinforce that rehabilitation clinicians developed innovative strategies to quickly adapt to multiple systems-level factors that were changing in the face of the COVID-19 pandemic. Future research is needed to assess the impact of innovations, remediate unintended consequences, and evaluate the implementation of promising innovations to respond to emerging healthcare delivery needs more rapidly.